Antitumor Activity of Larotrectinib in Esophageal Carcinoma with NTRK Gene Amplification. (23rd April 2020) - Hempel, Dirk; Wieland, Thomas; Solfrank, Beate; Grossmann, Vera; Steinhard, Johanna; Frick, Andrea; Hempel, Louisa; Eberl, Thomas; Gaumann, Andreas
Abstract: Background: Increasing knowledge about the genomic changes underpinning cancer development and growth has led to a rapidly expanding number of individualized therapies that specifically target these changes in a patient's tumor. Here we present a case report of a patient with metastatic esophageal carcinoma whose tumor harbored NTRK1 gene amplification and who received targeted systemic therapy with larotrectinib. At initial diagnosis, the patient presented with tumor obstruction of the middle esophagus, simultaneous liver and lung metastases, UICC IV and WHO performance status 3. Materials and Methods: The solid tumor genomic profiling test FoundationOne CDx (F1CDx) was used to detect clinically relevant genomic alterations that, in turn, might identify a targeted therapeutic approach if suggested by the findings. The patient was then treated with larotrectinib and had subsequent follow‐up biopsies. Results: Simultaneous biopsies of the primary tumor and liver lesions identified a metastatic squamous cell esophageal carcinoma. Comprehensive genomic profiling obtained from liver metastases identified numerous genomic alterations including amplification of NTRK1 . Owing to the reduced performance status of the patient, chemotherapy could not be applied and was denied. Although larotrectinib is only approved for the treatment of cancers with NTRK gene fusions, treatment was started and led to a shrinkage of the primary tumor as well as the liver and lung metastases within 6 weeks according to RECIST criteria accompanied by tumor marker decrease. The NTRK1 gene amplification was below the limit of detection in a subsequent liver biopsy. Conclusion: The use of comprehensive genomic profiling, specifically F1CDx, enabled the selection of a targeted therapy that led to a rapid reduction of the tumor and its metastases according to RECIST criteria. This case suggests that larotrectinib is not only effective in NTRK fusions but may be efficacious in cases with gene amplification. Key Points: Advances in precision medicine have revolutionized the treatment of cancer and have allowed oncologists to perform more individualized therapy. This case shows that larotrectinib could also be effective in cases of NTRK amplification of cancer. Today, there is only limited knowledge about NTRK alterations in squamous epithelial carcinoma of the esophagus. Longitudinal tumor sequencing during the course of the disease may allow for the detection of a molecular genetic cause once the tumor progresses. Additional actionable gene alterations may then be identified, which may provide the rationale for a therapy switch. Abstract : Knowledge of the efficacy of targeted therapy for TRK gene amplification is still lacking. This report presents the case of a patient with metastatic squamous cell esophageal carcinoma with NTRK1 gene amplification who received targeted therapy with larotrectinib with promising results.